The technique of training in the practical course of Russian directed to formation of skills of publicistic style (Eurasian Journal of Philology Science and Education, 2016)
Modern speech practice dictates certain requirements to the level of preparation of students. Besides forming linguistic and communicative competenses, there is a requirement in forming for the students of rhetorical competense. This, above all the public, always has been criticized, not less sharply criticized it today. Depleted centuries notions of speech quality must be supplemented by the criteria that determine the rights and obligations of the sender and the addressee [1]. On how concisely, precisely, it is appropriate, in accordance with the current situation of speech and logically formulated communicants thought it depends on the productivity of the communication process. Consequently, communicative and verbal ability to express their thoughts is essential to human activity. But this is the most important aspect in the study of the Russian language is underes timated, so the focus in the classroom is often only a letter, ie law relationship and interdependence of all kinds of speech activity in the course of their working and improving.
Keywords: communicative and rhetorical competenses; public speech; discussion; debates